Low back disorders : evidence-based prevention and rehabilitation - McGill, Stuart, ....- (Champaign (Ill.) : Human kinetics, 2007)
Access the latest research and applications to build effective prevention and rehabilitation programs for your patients or clients with Low Back Disorders: Evidence-Based Prevention and Rehabilitation, Second Edition. Internationally recognized low back specialist Stuart McGill presents original research to quantify the forces that specific movements and exercises impose on the low back, dispels myths regarding spine stabilization exercises, and suggests prevention approaches and strategies to offset injuries and restore function. Low Back Disorders: Evidence-Based Prevention and Rehabilitation, Second Edition, presents a clear exposition of back anatomy and biomechanics and demonstrates how to interpret the latest research on low back involvement for clinical applications. The text also contains detailed information on injuries associated with seated work and sport and ergonomic issues related to manual handling of materials. With Low Back Disorders: Evidence-Based Prevention and Rehabilitation, Second Edition, you will •gain valuable information on measured loading of the back during specific activities and apply it to avoid common—but counterproductive—practices in back rehabilitation; •learn how to analyze each patient's or client's unique physical characteristics and lifestyle factors to tailor preventive measures and treatments to individual needs; •learn how to help patients and clients progress through the stages of rehabilitation: corrective exercise, stability or mobility, endurance, and strength; and •acquire the information necessary to design an effective injury-prevention program.
This fully updated second edition expands knowledge of low back disorders and best practices in several areas. Enhanced algorithms guide progessive therapeutic exercise, and specially designed patient assessment provocation tests aid you in determining the cause of back troubles, guide your choices in the best ways to eliminate problems, and improve the development of appropriate activities for functional gain. Whereas the first edition focused on increasing spine stability, the second edition provides new information on dealing with both regional instability or mobility and regional stiffness present in individuals where most of the motion occurs at a single spinal segment. With an expanded repertoire of pain-free motion exercises and additional information on ways to find and adjust stabilization exercises, Low Back Disorders: Evidence-Based Prevention and Rehabilitation, Second Edition, offers you new tools to help your patients and clients achieve pain-free exertion. The text includes exercises and activities that provide a solid foundation of physical work in preparation for more advanced activities in sports and occupations. Also, the process of transitioning into performance exercise is outlined with an explanation of the critical stages of the performance pyramid, including the design of appropriate corrective exercise, building joint and whole-body stability, enhancing endurance, training true strength, and transitioning to ultimate performance.
Part I builds your knowledge of lumbar function and injury. Part II demonstrates how to use this knowledge to build evidence-based injury-prevention programs by assessing risks, creating ergonomic interventions, and training personnel. Part III focuses on improving rehabilitation techniques, including specific diagnostic and provocative tests, with specific therapeutic exercises proven to enhance performance and reduce pain through a continuum from corrective exercise to stability and mobility, endurance, strength, and power.
Keywords: Back Injuries -- Prevention & control; Back Injuries -- Rehabilitation; Backache; Evidence-Based Medicine; Evidence-based medicine; Lagerugpijn; Low Back Pain -- Prevention & control; Low Back Pain -- Rehabilitation; Rugklachten